Transoesophageal Doppler compared to central venous pressure for perioperative hemodynamic monitoring and fluid guidance in liver resection - El Sharkawy, Osama A. (Medknow Publications & Media Pvt Ltd, 2013)
PURPOSE: Major hepatic resections may result in hemodynamic changes. Aim is to study transesophageal Doppler (TED) monitoring and fluid management in comparison to central venous pressure (CVP) monitoring. A follow-up comparative hospital based study. METHODS: 59 consecutive cirrhotic patients (CHILD A) undergoing major hepatotomy. CVP monitoring only (CVP group), (n=30) and TED (Doppler group), (n=29) with CVP transduced but not available on the monitor. Exclusion criteria include contra-indication for Doppler probe insertion or bleeding tendency. An attempt to reduce CVP during the resection in both groups with colloid restriction, but crystalloids infusion of 6 ml/kg/h was allowed to replace insensible loss. Post-resection colloids infusion were CVP guided in CVP group (5-10 mmHg) and corrected flow time (FTc) aortic guided in Doppler group (>0.4 s) blood products given according to the laboratory data. RESULTS: Using the FTc to guide Hydroxyethyl starch 130/0.4 significantly decreased intake in TED versus CVP (1.03 [0.49] versus 1.74 [0.41] Liter; P<0.05). Nausea, vomiting, and chest infection were less in TED with a shorter hospital stay (P<0.05). No correlation between FTc and CVP (r=0.24, P > 0.05). Cardiac index and stroke volume of TED increased post-resection compared to baseline, 3.0 (0.9) versus 3.6 (0.9) L/min/m(2), P<0.05; 67.1 (14.5) versus 76 (13.2) ml, P<0.05, respectively, associated with a decrease in systemic vascular resistance (SVR) 1142.7 (511) versus 835.4 (190.9) dynes.s/cm(5), P<0.05. No significant difference in arterial pressure and CVP between groups at any stage. CVP during resection in TED 6.4 (3.06) mmHg versus 6.1 (1.4) in CVP group, P=0.6. TED placement consumed less time than CVP (7.3 [1.5] min versus 13.2 [2.9], P<0.05). CONCLUSION: TED in comparison to the CVP monitoring was able to reduced colloids administration post-resection, lower morbidity and shorten hospital stay. TED consumed less time to insert and was also able to present significant hemodynamic changes. Advanced surgical techniques of resection play a key role in reducing blood loss despite CVP more than 5 cm H(2)O. TED fluid management protocols during resection need to be developed.